Better Business Decisions Using Cost Modeling - Sower, Victor E (Business Expert Press, 2011)
Ebook from IG Library ; Information is power in supply chain operations, negotiations, continuous improvement programs, process improvement, and indeed in all aspects of managing an operation. Accurate and timely information can result in better decisions that translate into the improvement of bottom-line results. The development and effective use of cost modeling as a method to understand the cost of products, services, and processes can help drive improvements in the quality and timeliness of decision making. In the supply chain community, an understanding of the actual cost structures of products and services, whether with new or nonpartner suppliers, can facilitate fact-based discussions that are more likely to result in agreements that are competitively priced and with fair margins. Further, accurate cost models that are cooperatively developed between supply chain partners can form the basis for joint efforts to reduce non-value-added costs and provide additional focus toward operational improvement.